Efficient Optical Gain from Near‐Infrared Polymer Lasers Based on Poly[N‐9′‐heptadecanyl‐2, 7‐carbazole‐alt‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)]. Issue 15 (31st May 2018) - Xu, Yan; Hai, Gang; Xu, Haowen; Zhang, Haoran; Zuo, Zongyan; Zhang, Qi; Xia, Ruidong; Sun, Chen; Castro‐Smirnov, Jose; Sousaraei, Ahmad; Casado, Santiago; Osorio, Manuel R.; et al.
Abstract: State‐of‐the‐art near‐infrared lasers based on poly[ N ‐9′‐heptadecanyl‐2, 7‐carbazole‐ alt ‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)] (PCDTBT) and poly(9, 9‐dioctylfluorene‐ alt ‐benzothiadiazole) (F8BT) blends are reported. Polymer light‐emitting diodes (PLEDs) based on PCDTBT/F8BT blends with 30 wt% PCDTBT content exhibit a maximum radiance of 64.3 W sr −1 m −2 and external quantum efficiency of 2.11% with Commission Internationale de L'Eclairage (CIE) coordinates ( x = 0.69, y = 0.30). Using an optimal blend ratio of 15 wt% PCDTBT in F8BT, a maximum gain value of 28.2 cm −1 at 710 nm is achieved, a remarkable value given that PCDTBT is a low emissive polymer extensively employed as donor polymer in organic photovoltaics. The lowest amplified spontaneous emission (ASE) and laser thresholds exhibited by the blends are 590 nJ pulse −1 (21 µJ cm −2 ) and 63.1 nJ pulse −1 (201 µJ cm −2 ). Transient absorption spectroscopy confirms efficient Förster resonant energy transfer from F8BT to PCDTBT which, together with the large miscibility of PCDTBT in F8BT, enables PCDTBT emission enhancement and optical gain. Furthermore, a ternary blend system composed of F8BT, PCDTBT, and poly(3‐hexylthiophene) is demonstrated, in which the ASE wavelength can be tuned in a 60 nm range from 650 to 710 nm at a very low threshold level via control of the blend content ratio. Abstract : Poly[ N ‐9′‐heptadecanyl‐2, 7‐carbazole‐ alt ‐5, 5‐(4′, 7′‐di‐2‐thienyl‐2′, 1′, 3′‐benzothiadiazole)] (PCDTBT) is demonstrated as an optical gain medium by blending it with poly(9, 9‐dioctylfluorene‐ alt ‐benzothiadiazole) (F8BT). Optimizing the blending ratio of PCDTBT/F8BT leads to efficient red‐emission polymer light‐emitting diodes and PCDTBT optical gain to occur. 15–20 wt% PCDTBT doping of PCDTBT/F8BT yields high‐performance near‐infrared lasers due to a sub‐picosecond energy transfer from F8BT to PCDTBT.